Spontaneous Formation of Melanin from Dopamine in the Presence of Iron - David M. Hedges; Jordan T. Yorgason; Andrew W. Perez; Nathan D. Schilaty; Benjamin M. Williams; Richard K. Watt; Scott C. Steffensen (MDPI AG, 2020)
Parkinson's disease is associated with degeneration of neuromelanin (NM)-containing substantia nigra dopamine (DA) neurons and subsequent decreases in striatal DA transmission. Dopamine spontaneously forms a melanin through a process called melanogenesis. The present study examines conditions that promote/prevent DA melanogenesis. The kinetics, intermediates, and products of DA conversion to melanin in vitro, and DA melanogenesis under varying levels of Fe3+, pro-oxidants, and antioxidants were examined. The rate of melanogenesis for DA was substantially greater than related catecholamines norepinephrine and epinephrine and their precursor amino acids tyrosine and l-Dopa as measured by UV-IR spectrophotometry. Dopamine melanogenesis was concentration dependent on the pro-oxidant species and Fe3+. Melanogenesis was enhanced by the pro-oxidant hydrogen peroxide (EC50 = 500 μM) and decreased by the antioxidants ascorbate (IC50 = 10 μM) and glutathione (GSH; IC50 = 5 μM). Spectrophotometric results were corroborated by tuning a fast-scan cyclic voltammetry system to monitor DA melanogenesis. Evoked DA release in striatal brain slices resulted in NM formation that was prevented by GSH. These findings suggest that DA melanogenesis occurs spontaneously under physiologically-relevant conditions of oxidative stress and that NM may act as a marker of past exposure to oxidative stress.